Religious faith penetrates the last years of life. Issue 9 (21st October 2018) - Aboulela, Leila
ABSTRACT: Memento Mori champions the elderly as heroes and heroines and brings them centre stage. In the epilogue to the novel, Spark cites Penny Catechism. Reflecting on our mortality should make us pause before we sin, it should make us curb our cruelties and greed. The genius of Spark's novel is how the behaviour of the elderly who refuse to remember death is made comic. Few writers can make us laugh about religious practice without belittling or dismissing. And even fewer can pull such jokes off with good taste. For today's secular readers, the subtlety of the religious elements of the novel might easily be overlooked. In today's literary climate the idea has taken hold that the novel has replaced religion. Muriel Spark's life and body of work refutes this argument. Spark accepted Catholicism before writing Memento Mori and the novel is a direct reflection of her faith. However, Memento Mori is almost devoid of the mention of spirituality or the Divine. For clues to Muriel Spark's religious vision of the world and her reticence to impose it on the reader, it is best to read her longest novel, The Mandelbaum Gate, described by the New York Times as 'overtly Catholic'. Like Spark, the protagonist is a half-Jewish, Catholic convert. Near the end of the novel she says, '…either religious faith penetrates everything in life or it doesn't.